Mediator Motivasi Belajar Intrinsik terhadap Prestasi Belajar Statistika - Adi Putra Hidayatullah; Asmadi Alsa (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
This research aimed to examine cognitive learning as a mediator of the relationship between intrinsic learning motivation and statistics learning achievement. The data were collected through the motivation scale of intrinsic learning and cognitive learning strategy. Statistics learning achievement was measured through the grades of mid-semester exam and final exam. The subjects in this research were 208 undergraduate students who took a statistics class.  Multiple regression analysis through mediation model indicated that cognitive learning strategy was a partial mediator for the motivational role of intrinsic learning on statistics learning achievement (p<0.05). However, among four forms of cognitive learning strategy, only rehearsal and organizational learning strategies were capable of predicting statistics learning (p<0.05).